2011
DOI: 10.1371/journal.pone.0027767
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Keratin 8 Phosphorylation Leads to Increased Tumor Progression and Correlates with Clinico-Pathological Parameters of OSCC Patients

Abstract: BackgroundKeratins are cytoplasmic intermediate filament proteins expressed in tissue specific and differentiation dependent manner. Keratins 8 and 18 (K8 and K18) are predominantly expressed in simple epithelial tissues and perform both mechanical and regulatory functions. Aberrant expression of K8 and K18 is associated with neoplastic progression, invasion and poor prognosis in human oral squamous cell carcinomas (OSCCs). K8 and K18 undergo several post-translational modifications including phosphorylation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
33
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 45 publications
7
33
0
1
Order By: Relevance
“…Genome-wide association studies have also identified single nucleotide polymorphisms in the human K5 locus that are correlated with an increased lifetime risk of developing basal cell carcinoma (Stacey et al 2009). As already discussed above, keratin phosphorylation, affecting cell motility, is also implicated in cancer cell migration and metastasis (Alam et al 2011;Busch et al 2012).…”
Section: Keratins and Cancermentioning
confidence: 83%
See 1 more Smart Citation
“…Genome-wide association studies have also identified single nucleotide polymorphisms in the human K5 locus that are correlated with an increased lifetime risk of developing basal cell carcinoma (Stacey et al 2009). As already discussed above, keratin phosphorylation, affecting cell motility, is also implicated in cancer cell migration and metastasis (Alam et al 2011;Busch et al 2012).…”
Section: Keratins and Cancermentioning
confidence: 83%
“…K8 phosphorylation is implicated in both inhibition and promotion of cell migration, depending on cell type and stimulus (Chung et al 2013). It is linked to increased migration in pancreatic and gastric cells but decreased migration in oral squamous carcinoma cells (Alam et al 2011;Busch et al 2012), highlighting the stimulus-specific function of phosphorylation. In response to cell stress (such as under UV radiation and in apoptosis) or disease (psoriasis and squamous cell carcinoma), K4, K5 and K6 undergo phosphorylation, causing keratin filaments to be disassembled into granules, allowing for short-term regulation of epithelial cell plasticity (Fois et al 2013).…”
Section: Post-translational Modificationsmentioning
confidence: 99%
“…Numerous vimentin phosphorylation sites have been identified in vivo 8 and they appear to promote its pro-migratory function, in part by enhancing recycling 87 and activation 88 of integrins. K8 phosphorylation at Ser432 has been linked to increased migration of pancreatic and gastric cells 89 but decreased migration of oral squamous carcinoma cells 90 , highlighting a context-specific function of this phospho-residue. Increased cellular elasticity caused by the bioactive lipid sphingosylphosphorylcholine, 91 which was used in the study of pancreatic and gastric cells, likely orchestrates a unique migratory program that is dependent on pSer432-mediated perinuclear K8 and K18 re-reorganization.…”
Section: If Phosphorylation: Multifunctional Ptmmentioning
confidence: 99%
“…An inhibitory influence for K8 towards cell migration is suggested by studies in which pancreatic cancer cells [89] and a poorly invasive subclone of MDA-MB-468 breast cancer cells was subjected to K8 knockdown [90], a highly invasive subclone of MDA-MB-435 breast cancer cells was made to overexpress K8 [90], and when KLE endometrial cancer cells and HepG2 hepatocellular cancer cells were subjected to K8/K18 silencing [91]. Other studies related the loss of K8 phosphorylation at either Ser 73 or Ser 431 to increase migration and/or metastatic potential for oral squamous cell carcinoma cells [92] and colorectal cancer cells [93]. The opposite outcome, i.e., K8-dependent stimulation of cell migration, was inferred from the impaired collective migration of hepatoma cells following K8 silencing [35].…”
Section: The Complex Relationship Between Keratins 8/18 and Epitheliamentioning
confidence: 99%